Implications of Instituting an Enhanced Recovery after Surgery Pathway in Patients Receiving Chemotherapy in Microsurgical Breast Reconstruction. Issue 1 (30th September 2020) - Haddock, Nicholas T.; Garza, Ricardo; Boyle, Carolyn E.; Teotia, Sumeet S.
Abstract : Background: Neuropathy is a common side effect of chemotherapeutic agents. Manifestations of chemotherapy-induced neuropathy can present in a myriad of fashions, ranging from numbness, tingling, and pain to motor weakness and autonomic dysfunction. 1 Given the nature of breast reconstruction, a significant portion of the patients have a history of chemotherapy exposure; its effect on postoperative pain management has not been previously explored. Methods: This study is a retrospective review of patients who underwent deep inferior epigastric perforator flap breast reconstruction performed by the two senior authors from January of 2016 to September of 2019. The patients were separated into two groups, before and after enhanced recovery after surgery. The primary outcome observed was postoperative opioid consumption, measured as oral morphine equivalents; p values were obtained through univariate linear regression. Results: In total, 256 patients were analyzed, of which 113 had chemotherapy exposure. The difference between opioid consumption in patients in the pre–enhanced recovery after surgery group without and with chemotherapy exposure was statistically significant (211.5 mg versus 278.5 mg; p = 0.0279). There was no difference between opioid consumption with regard to chemotherapy history in the enhanced recovery after surgery group (137.4 mg versus 133.0 mg; p = 0.7251). Conclusions: Patients with chemotherapy exposure required more opioids to be comfortable. It is unknown whether this difference is secondary to increased pain or less effectiveness of opioids. Further research is necessary to assess whether there are better ways to address pain postoperatively in patients with chemotherapy exposure. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.